Clinical significance of serum miR-98-5p in children with Mycoplasma pneumoniae infection complicated with digestive system damage - Li, Ying; Jia, Wei; Huang, Jiayang; Liu, Jian (Immunobiology (1979), 2025)
Studies have shown that serum microRNA detection holds significant potential in improving the diagnostic accuracy of mycoplasma pneumoniae pneumonia (MPP). To investigate the expression and clinical value of miR-98-5p in children with Mycoplasma pneumoniae (MP) infection complicated with diarrhea. A total of 122 children diagnosed with MPP were selected as study subjects, and 80 healthy children were selected as controls. Real-time quantitative PCR (RT-qPCR) was used to detect the expression of miR-98-5p. Receiver operating characteristic (ROC) curve was used to determine the diagnostic value of miR-98-5p. The risk factors for MPP with diarrhea were analyzed by means of a logistic regression model. THP-1 cell models with miR-98-5p overexpression and knockdown were established to investigate the potential mechanisms of miR-98-5p in MP infection. Serum miR-98-5p expression is decreased among children having MPP, and it has a negative correlation with the logMP-DNA level. The miR-98-5p level in children with MPP accompanied by diarrhea is lower compared to that in children with MPP alone. miR-98-5p demonstrates promising diagnostic potential for MPP complicated with diarrhea, and serves as a risk factor for diarrhea in MP-infected children. TargetScan database prediction showed that potential target genes of miR-98-5p, including Synaptotagmin 1 (SYT1) and Tribbles pseudokinase 1(TRIB1), are both associated with digestive system injury induced by MP infection. The expression of serum miR-98-5p is decreased in children with MPP complicated by diarrhea, and it may become a diagnostic biomarker. •Serum miR-98-5p expression decreased in children with MPP complicated by diarrhea.•Serum miR-98-5p is correlated with logMP-DNA level in children with MPP.•Low miR-98-5p expression is a risk factor for MPP complicated by diarrhea.•miR-98-5p plays a role in MP infection by targeting SYT1.